The importance of early detection of suicidal ideation in the elderly in the pandemic (Research, Society and Development, 2022)
The year 2020 was marked by the pandemic of coronavirus (Covid-19), which had repercussions in the various spheres of society as a whole. The containment measures used, however, such as social isolation, generated significant impacts, especially the emotional damage in the lives of many, especially in the elderly. This article aims to analyze scientific production in an evidence-based medicine on the importance of early detection of suicidal ideation in the elderly in the pandemic.  This is an Integrative Literature Review, looking for articles in the Virtual Health Library (VHL), through the combination of elderly controlled descriptors, suicide and pandemic. Ten articles were in the corpus, between 2019 and 2021, in the Portuguese, English and French. In addition, three (3) thematic axes were identified: (I) Possible reasons for suicidal ideation; (II) Risk factors and suicide prevention strategies in the elderly during Covid-19 and (III) Repercussion and media assistance in the Covid-19 pandemic. The high incidence of suicide in the elderly population and its important intercession with the reality faced by the coronavirus pandemic was made quite clear in the present study. Thus, strategies for building a support network for this vulnerable population must be drawn up.